IMPLEMENTATION OF THE CONSTITUTIONAL RIGHT TO APPEAL JUDICIAL DECISIONS WITHIN THE FRAMEWORK OF ADMINISTRATIVE JUSTICE - Yakovenko , Eugen (Collection of scientific papers «ΛΌГOΣ», 2025)
The right to appeal in administrative proceedings is a key element of constitutional guarantees and an effective mechanism for protecting individuals’ rights against unlawful or unreasonable actions by public authorities. Its implementation relies heavily on the legal standards of evidence collection and assessment. These standards must align with constitutional norms and ensure that public authorities respect procedural fairness during legal proceedings [1, p 33-40]. The process of appealing administrative decisions is particularly sensitive when involving tax disputes, where state revenue interests intersect with citizens’ rights. Ensuring lawful grounds for document-based audits is essential to preserve the balance between fiscal oversight and individual protection [2, p. 179-188].